Possibilities of long-range forecast of weather conditions over the Antarctic peninsula - Tymofeyev, V. E. (Ukrainian Antarctic Journal, 2015)
The paper analyzes the impact of the El Niño-Southern Oscillation on the climatic conditions of the Antarctic Peninsula via spatial correlations, as well as studies into atmospheric circulation. Change in the El Niño-Southern Oscillation to the great extent determines regional climate trends. In order to improve methods for seasonal forecasts, the use of the El Niño 1-2 index eastern Pacific Ocean is recognized, based on synchronous and asynchronous correlations. Scheme for Academik Vernadsky station is presented. During the warm phase anticyclogenesis is typically developing in the Pacific sector of the Antarctic, and in the years of La Nina — cyclogenesis is predominant. It is noted that each manifestation of El Niño events are unique, with different localization of pressure systems in the Antarctic Peninsula’ the peninsula is located at the boundary of the area of influence of different centers of atmospheric action. The results can be used to improve understanding of atmospheric mechanisms of regional climate variability and improving the methods of weather forecasting.